Ethnobotany and erosion of food plant knowledge in culinary traditions of Thai Song DamEthnobotany and erosion of food plants knowledge in culinary traditions of Thai Song Dam - Nguanchoo, Varangrat; Klomjai, Pornnapa; Kwangthong, Aingkate; Meekeaw, Butsakon; Maneenoi, Arisa (Health Science, Science and Technology Reviews, 2025)
Food consumption patterns have increasingly aligned with urbanized dietary trends, replacing local vegetables with commercially driven crops and contributing to the progressive erosion of traditional food practices. Thai Song Dam is an ethnic group that places importance on food. This research aims to document the food plants used in the traditional cuisine of the Thai Song Dam community in Khao Yoi district, Phetchaburi province. Data were collected through participatory observation with Thai Song Dam food experts. The study identified nine significant dishes of the Thai Song Dam and a total of 16 plant species. Zanthoxylum rhetsa is an important plant ground into curry paste to provide a unique aroma and a spicy and numbing flavor. Most Thai Song Dam villagers have knowledge of nearly all food plant species; however, some people have never consumed some plant species such as the pseudostem of Musa balbisiana and Wolffia globosa. A study investigating the factors associated with the erosion of food plant knowledge within the community employed structured interviews with 30 Thai Song Dam villagers. The findings indicated that socioeconomic factors did not significantly influence the number of plant species recognized by the villagers. In contrast, factors such as age, level of education, and culinary skills were correlated with the number of plant species actually consumed. Understanding these factors related to knowledge erosion is essential to inform targeted conservation strategies within the community, thereby supporting local food security and preserving plant biodiversity.